Yoruba Orature: The Fundamental Basis for Teaching Yoruba Numeral (Global Journal of Human-Social Science, 2022)
Without mincing words, there is a gradual loss of long-aged tradition, a method of equipping young ones for life. In Yorùbá traditional setting, the teaching of Yorùbá numerals remains an authentic means of transmitting culture from one generation to another. This paper attempts to examine that Yorùbá traditional education is deeply rooted in Yorùbá orature. Equally, it shows that the education system had been part and parcel of the society and it is not the training given in modern education but education which the indigenous black people of Africa offered. Additionally, the paper establishes that Yorùbá orature serves both recreational as well as educational purposes to prove that the use of Yorùbá orature is a fundamental basis for teaching the young ones the Yorùbá numerals as embedded in the culture and tradition of the people. Apart from this immediate and apparent function of teaching the young ones, the teaching of Yorùbá numerals initiates child(ren) into the various phases of life. This research work adopted both primary and secondary research methods.
Keywords: yorùbá orature; yorùbá numerals; traditional education; western-education; society; theory; culture; children